Digital adaptation of texts in hungarian teacher training - Gonda Zsuzsa; Гонда Жужа („RIK-U” Kft., 2019)
Abstract. The following study demonstrates digital innovative processes and the use of ICT in pedagogy at the Faculty of Humanities at ELTE. The first aim of the presentation is to discover opportunities to develop the ICT competencies of Hungarian teacher trainee students during different stages of their education. The second aim of the presentation is to demonstrate digital methodological techniques, which are directly applicable in methodology courses. During methodology courses the ICT competencies of teacher trainees can be developed at different levels (elementary, complex, professional) with the help of text adaptation practices, which also help to extend their knowledge in other fields of their major education. The presented practices apply the formal, substantive and conceptual features of digital texts; reading strategies of digital texts; as well as the constructivist approach of pedagogy through the use of web 2.0 applications.

A tanulmány a magyartanárképzésben zajló digitális innovatív folyamatokat, az IKT pedagógiai alkalmazására való törekvést mutatja be az ELTE BTK gyakorlatában. A tanulmány egyik célja, hogy feltérképezze, a tanárképzés különböző szakaszaiban milyen lehetőségek adódnak a magyar szakos hallgatók IKT-kompetenciájának fejlesztésére; másik célja, hogy olyan digitális módszertani megoldásokat mutasson be, amelyek közvetlenül alkalmazhatók szakmódszertani kurzusok keretében.
Обробка цифрового тексту у підготовці угорських філологів
Digitális szövegfeldolgozás a magyartanárképzésben
http://kmf.uz.ua/wp-content/uploads/2019/04/Final-Pedagogical_conf_2019_03_28-29.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00007073
Keywords: ICT competencies; digital text; digital literacy; teacher training